2013
DOI: 10.1007/s10286-013-0201-2
|View full text |Cite
|
Sign up to set email alerts
|

Gravimetry in sweating assessment in primary hyperhidrosis and healthy individuals

Abstract: ObjectiveThough hyperhidrosis is generally considered a subjectively perceived disease, it seems more and more doubtful that merely subjective evaluation is sufficient to qualify the patient to surgery. The aim of this study was to develop further gravimetry as a method of evaluation of sweating intensity and determination of the applicability of it in post-operative follow-up of primary hyperhidrosis (PHH) patients.MethodsTotal of 1,485 gravimetry assays has been performed in 343 patients treated for hyperhid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 15 publications
0
23
1
Order By: Relevance
“…Attempts to quantify the effect of treatment in PH have been numerous, as the indices of satisfaction with treatment and quality of life are purely subjective . Besides, some methods are used during surgery to verify in real time the disruption of sympathetic activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to quantify the effect of treatment in PH have been numerous, as the indices of satisfaction with treatment and quality of life are purely subjective . Besides, some methods are used during surgery to verify in real time the disruption of sympathetic activity .…”
Section: Introductionmentioning
confidence: 99%
“…Minor's starch‐iodine test is useful to delineate the areas of hyperhidrosis; it has been used for follow‐up, but this is a semiquantitative method, cumbersome to apply (particularly in outpatients) and time‐consuming . Gravimetry is preferred by some, but has the disadvantages of high variability of sweat production and difficulty in measuring smaller amounts of sweat . Special appliances that quantitatively measure the amount of sweat excreted (transepidermal water loss equipment, evaporation cameras) are the most accurate but expensive and assess a small area at a time …”
Section: Introductionmentioning
confidence: 99%
“…Correspondence research, which constitutes the majority of PHH epidemiological analyses, are burdened with interpretation error made by respondent. As demonstrated in papers of our team, the subjective evaluation of hyperhidrosis prevalence in population often significantly differs from actual data obtained with objective methods (9,10,11). On the basis of research conducted by our team on 253 students it has been demonstrated that primary palmar hyperhidrosis may occur even from 4.7% of people (subjective declaration) to 7.1% (gravimetric screening method), whereas axillary hyperhidrosis from 11% (subjective declaration) to 16.2% (gravimetric assessment) (10).…”
Section: R E V I E W P a P E R S Primary Hyperhidrosis -Pathogenesismentioning
confidence: 91%
“…Net weight of secreted sweat is calculated as the difference between the gross weight (swab weight after the test) and tare (swab weight before the test). The result is divided by the total surface of the subject's body in order to minimize the impact of the body build on the result (11,20). Reference values for the different areas of the body have been determined in the study conducted by our team on over 400 volunteers (11).…”
Section: Diagnosis Of Primary Hyperhidrosismentioning
confidence: 99%
See 1 more Smart Citation